Texts of the passion : Latin devotional literature and medieval society - Bestul, Thomas H. (Thomas Howard), 1942- (Middle Ages series., 1996)
In Texts of the Passion, Thomas H. Bestul constructs the literary history of the Latin Passion narratives, placing them within their social, cultural, and historical contexts. He examines the ways in which the Passion is narrated and renarrated in devotional treatises, paying particular attention to the modifications and enlargements of the narrative of the Passion as it is presented in the canonical gospels. Of particular interest to Bestul are the representations of Jews, women, and the body of the crucified Christ. Bestul argues that the greatly enlarged role of the Jews in the Passion narratives of the twelfth and thirteenth centuries is connected to the rising anti-Judaism of the period.